Home away from home : a study on the family staycation experience. - Ng, Sharon Xumin. (2013)
The busy Singaporean lifestyle has resulted in more families choosing to take a quick break in a local hotel instead of travelling overseas. Data collected using qualitative methods from a sample of 20 respondents aged from 21 to 59 provided insights into the social construction of the ‘family gaze’ and the influence of staycations on family cohesiveness. This study aims to draw the link between the concept of the gaze and family leisure studies. Findings showed the interplay between the ‘family gaze’, core and balance model in leisure studies and purposive leisure leading to the outcome of increased feelings of family bonding during a staycation.